WOMEN SAFETY DEVICE WITH GPS TRACKING ALERTS (International Journal of Food and Nutritional Sciences, 2022)
Women’s safety plays a very vital role now a days due to rising crimes against women. To help resolve this issue we propose a GPS based women’s safety system that has dual security feature. The proposed system consists of a dual alert that is buzzer and message is sent through GSM. This system can be turned on by a woman in case she even thinks she would be in trouble. This Project presents a women safety detection system using GPS and GSM modems. The system can be interconnected with the alarm system and alert the neighbors. This detection and messaging system is composed of a GPS receiver, GPS Receiver gets the location information from satellites in the form of latitude and longitude. The user receives the information from GSM which receives the processed information from the Microcontroller. A GSM modem is interfaced to the MCU. The GSM modem sends an SMS to the predefined mobile number. When a woman is in danger and in need of self-defense then she can press the switch, which is allotted to her. By pressing the switch, the entire system will be activated then immediately a SMS will be sent to concern person with location using GSM and GPS.